Evaluating Local Community and Government Authority engagement in developing the Tourism business in Uzbekistan - Oppokkhonov Nurmukhammad; Amonboev Mahammadsidik; Matyakubov Umidjon; Chuponov Sanat; Ermetova Ikbol (BIO Web of Conferences, 2024)
A research study was carried out to investigate the extent to which local communities and government authorities are involved in tourism development, with the objective of promoting sustainable practices that are mutually beneficial. Although attempts have been made to incorporate local communities in the tourism sector, there is insufficient research on their viewpoints and level of participation, particularly in Uzbekistan. The purpose of this research is to appraise the perceptions of local government authorities regarding the progress of tourism, gauge their current participation in the field, comprehend their thoughts on the government’s responsibility in tourism development, and investigate their stance on contributing funds to the local community. This study focuses on Uzbekistan as the research area and aims to investigate the views of local communities and government authorities on tourism development. Additionally, the study seeks to identify opportunities for enhancing local community engagement in tourism in Uzbekistan regions. The objectives of this research are as follows: 1) to evaluate the viewpoints of government officials in Uzbekistan regions regarding the progress of tourism; 2) to examine the level of involvement of local government in the tourism sector; and 3) to scrutinize the perspectives of local authorities on the role of the government in the development of tourism and 4) examine the perspectives of local authorities on contributing revenue to the local community.